Professional Development of Teachers with ICT - Ali, Mohd. Mamur (Indian Journal of Educational Technology, 2019)
The increasing availability of Information and Communication Technologies (ICT) presents teachers with exciting opportunities to transform pedagogical practices. The demand on teachers to integrate ICT into their teaching and learning programs is high and places additional pressures on teachers in an already challenging profession. The pervasive nature of ICT in daily life has made society reliant on systems and tools that provide challenges for the way people think and work. Students entering the workforce need not only to be equipped with the skills to use those new technologies, but also to be flexible, adaptable, and multiskilled. They need to operate in an information age that requires them to be: information literate, inventive thinkers, and skilled communicators. This has placed great pressure on educators to provide students with opportunities to develop the skills required to engage effectively in a progressive society and become life-long learners. First and foremost, teachers have to enhance their own ICT competencies and then have to bring changes in their classroom with the utilization of ICTs. The professional development of Teachers can be made possible through various online ICT and subject specific courses which are available on SWAYAM, ITPD and ICT curriculum portals.